Caracterización fenotípica del cerdo criollo en los cantones Paltas, Olmedo y Chaguarpamba de la provincia de Loja - Peralta Sánchez, Roque Luis (2016)
Phenotypic characterization of the creole pig was conducted in the Paltas, Olmedo and Chaguarpamba cantons province of Loja, in the period 2015-2016. A registration was applied for data collection during field work, a sample of 64 creole pigs, more than one year of age, of both sexes, selected through non-probability snowball method; measurements were made using materials zoometric (zoometric cane, drill compass, measuring tape and digital scale). Phenotypic characterization understood zoometric 17 measures, characteristics fanerópticas 7, and calculating zoometric indices 9. The main indicators of the variable zoometric measures with their respective averages for the three cantons were: live weight (PV) 54.50 ± 26.81 kg, head length (LCZ) 22.27 ± 4.13 cm, width head (ACZ) 16.0 ± 3.0 cm, length of the muzzle (face, LH) 14.62 ± 2.58 cm, width of muzzle (face, AH) 10.28 ± 1.95 cm, length rump (LGR) 20.54 ± 4.77 cm, width of the croup (AGR) 18,90 ± 5,16 cm, diameter bicostal (DBC) 21.98 ± 4.92 cm diameter back sternal (DDE ) 35.13 ± 9.72 cm, height at the withers (ALC) 58.87 ± 8.70 cm, height at the croup (ALG) 61.67 ± 8.19 cm, raised the birth of the tail (ANC ) 49,57cm ± 7.28, longitudinal diameter (DL) 62.44 ± 7.94 cm, chest circumference (PTO) 78.90 ± 19.53 cm, perimeter cane (PCA) 13.98 cm ± 2 , 31, ear length (LO) 16.21 ± 3.05 cm, and width of the ear (AO) 13.41 ± 3.53 cm.